Sistem Backend dari Aplikasi Mobile dan Website untuk Sistem Registrasi, Reservasi, dan Identifikasi Penumpang Shuttle Bus UK Petra - Michelle Christiana Chandra; Rolly Intan; Liliana Liliana (Universitas Kristen Petra, 2022)
In 2022, Petra Christian University (PCU) launched its shuttle bus program exclusive to the academic community of PCU. This bus operates by picking up and dropping off passengers on the route of West Surabaya – PCU and vice versa. There are overwhelmingly many more members of the academic community of PCU residing in West Surabaya compared to the capacity of the shuttle bus. Registration, reservation, and identification systems are necessary to resolve this problem. The registration system ensures that the passengers are members of the academic community of PCU. The reservation system supports passengers in booking seats for the desired trips. The identification system authenticates the passengers when boarding the shuttle bus. The PCU shuttle bus program is operational and has been using the deployed application properly. Every function and API in the application passes the designed feature testing and matches the appropriate expectations. A survey was conducted of 76 passengers and 1 admin and 2 drivers were interviewed. From 76 passenger respondents, the average satisfaction score is 4.259 out of 5. From the 2 driver interviews, the application received a score of 8 and 10 out of 10. And lastly, the average satisfaction for the admin system and website is 4.75 out of 5.